Application of Infrared to Biomedical Sciences - Ng, Eddie YK.; Etehadtavakol, Mahnaz; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book covers the latest updates in the application of infrared to biomedical sciences, a non-invasive, contactless, safe and easy approach imaging of skin and tissue temperatures. Its diagnostic procedure allows practitioners to identify the locations of abnormal chemical and blood vessel activity such as angiogenesis in body tissue. Its non-invasive approach works by applying the technology of the infrared camera and state-of-the-art software, where high-resolution digital infrared imaging technology benefits highly from enhanced image production, standardized image interpretation protocols, computerized comparison and storage, and sophisticated image enhancement and analysis. The book contains contributions from global prominent scientists in the area of infrared applications in biomedical studies. The target audience includes academics, practitioners, clinicians and students working in the area of infrared imaging in biomedicine.
Breast Imaging -- Rheumatology -- Inflammation -- Controlling Temperature in Laser Therapy -- Thyroid Gland -- Sports Medicine -- Dentistry -- Diabetic Neuropathic Foot -- Skin Cancer Detection -- Detecting Fever -- Regional Anesthesia -- Plastic Surgery -- Determining the Functionality of Anti-allergy Medicine -- Injury -- Pain / Trauma -- Peripheral artery Disease -- Evaluation of Mental Work -- Scrotal imaging.
Keywords: Biomedical engineering; Medical physics; Radiology; Biotechnology; Regenerative medicine; Biomedical Engineering and Bioengineering; Medical Physics; Radiology; Biotechnology; Regenerative Medicine and Tissue Engineering